Transformation of retail trade as a component of distribution sector in terms of differently directed perspectives - Tkachenko , S. O. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The article considers the development of the trade sector. The essence of distribution in the operating cycle of the social product in the form of a commodity has been determined and its significance as one of the main indicators of the economic condition not only of the certain sectors of the national economy but the country as a whole has been examined. The purpose of the article is to study the specifics of the financial relations of the sphere of circulation and distribution channels, the relationship between the dynamics of the volume of retail trade turnover and the development of the trade infrastructure. The subjects of the sphere of circulation are the main participants in the distribution channels of goods, and accordingly, in the financial flows, providing direct sales services in their operation process, that gives us the right to argue that it is the trade and the service sector that have real opportunities for the future expansion of their activities. The author has defined peculiar features of the work of the entities functioning in the distribution system, which consists in combining productive and non-productive transactions concerned with the change of ownership types, i.e., directly with the sales of products, which requires additional study in terms of transformational reorganizations. The issues of economic entities’ functioning, asset and capital formation, sales, financial and economic security have been considered. The directions for the development of the market mechanism of the distribution sector in the reproduction process have been worked out and the feasibility of introducing additional methods to investigate dynamic changes and fluctuating data has been proved. The author has come to the conclusion that the degree of the development of the distribution sector is one of the main indicators of the economic condition not only of certain sectors of the national economy and the country as a whole, but it also characterizes the social and economic state of households that determine solvent demand.